Factorial Structure of the Movement Assessment Battery for Children Test-Second Edition in Preschool Children - Psotta, Rudolf; Brom, Ondřej (Perceptual and motor skills, 2016)
The Movement Assessment Battery for Children-Second Edition is one of the most frequently used tests for assessment of the fundamental motor skills in children. However, there is the question which sensorimotor functions are really captured by the tasks involved in the test for the preschool (3-6 years) children (age band 1). The aim of the study was to examine the factorial structure of the age band 1 test. Results of the testing by the age band 1 in a sample of three- to- six-year-old children (N = 399; 202 boys, 197 girls) were put to confirmatory factor analysis. The results of the study proved the three-specific factor structure of the age band 1. Thus, within the assessment of a child's overall motor proficiency, the motor competence profile including manual dexterity, aiming and catching, and balance abilities can be identified in three- to six-year-old children.
Keywords: Psychometrics; Male; Child Development; Child, Preschool; factor structure; vývoj dítěte; Child; dítě; mužské pohlaví; Motor Skills; faktorová analýza statistická; Neuropsychological Tests; Factor Analysis, Statistical; předškolní dítě; lidé; ženské pohlaví; psychometrie; test; Movement Assessment Battery for Children; Humans; motor abilities; neuropsychologické testy; motorické dovednosti; Female